2016
DOI: 10.1089/ars.2014.6187
|View full text |Cite
|
Sign up to set email alerts
|

Effective Killing of Cancer Cells Through ROS-Mediated Mechanisms by AMRI-59 Targeting Peroxiredoxin I

Abstract: Our results highlight a promising strategy for cancer therapy that preferentially eradicates cancer cells by targeting the PrxI-mediated redox-dependent survival pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…The mouse model studies have shown that Prx I deficiency induces various malignant tumors (Neumann et al, 2003) and aggravates the KRAS-induced spontaneous lung tumorigenesis (Park et al, 2013). However, the chemical inhibition of Prx I activity was shown to cause death of the lung carcinoma cells through in vitro culture and acute tumor xenograft (Yang et al, 2015). In this study, we demonstrate that Prx I is a residential nucleosomal protein that prevents the oxidative DNA damage.…”
Section: Prx I-dependent Apoptosis Regulationmentioning
confidence: 55%
“…The mouse model studies have shown that Prx I deficiency induces various malignant tumors (Neumann et al, 2003) and aggravates the KRAS-induced spontaneous lung tumorigenesis (Park et al, 2013). However, the chemical inhibition of Prx I activity was shown to cause death of the lung carcinoma cells through in vitro culture and acute tumor xenograft (Yang et al, 2015). In this study, we demonstrate that Prx I is a residential nucleosomal protein that prevents the oxidative DNA damage.…”
Section: Prx I-dependent Apoptosis Regulationmentioning
confidence: 55%
“…31, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 It is also well accepted that the efficacy of many anticancer therapies, including chemotherapeutics and radiotherapy, largely depends on their ability to induce ROS accumulation and evoke cell toxicity and death. 14, 50, 51, 52, 53, 54, 55, 56 The high levels of oxidative stress normally associated with malignant progression represent tumor-specific alteration that makes cancer cells vulnerable to further elevation of ROS and strongly dependent on their antioxidant defenses. Both extrinsic and intrinsic factors contribute to generate a persistent amount of high ROS levels in tumors.…”
Section: Ros Homeostasis and Redox Cofactors In Normal And Tumor Cellsmentioning
confidence: 99%
“…Prdxs have been reported to be differentially expressed in human pancreatic cancer [7], Burkitt lymphoma [8], lung carcinoma [9], colorectal carcinoma [10], prostate cancer [11], myeloma [12], and leukemia [13]. Prdx2, a typical 2-Cys peroxiredoxin, has higher expression levels in tumorous colon tissues compared with the corresponding normal non-tumor tissues [14], and Prdx2 knockdown inhibits cell growth and stimulates apoptosis [10].…”
Section: Introductionmentioning
confidence: 99%